Identification and Verification of Necroptosis-Related Gene Signature and Associated Regulatory Axis in Breast Cancer - Hu, Ting; Zhao, Xiangwang; Zhao, Yanxia; Cheng, Jing; Xiong, Jie; Lu, Chong (Frontiers in Genetics, 2022)
Background: Breast invasive carcinoma (BRCA) is the second leading cause of malignancy death among women. Necroptosis is a newly discovered mechanism of cell death involved in the progression and prognosis of cancer. The role of necroptosis-related genes (NRGs) in BRCA were still a mystery. Methods: LASSO cox regression analysis was performed to construct a prognostic necroptosis-related signature. A ceRNA was constructed to explore the potential lncRNA-miRNA-mRNA regulatory axis in BRCA. Results: A total of 63 necroptosis-related genes were differentially expressed in BRCA. We also summarized genetic mutation landscape of NRGs in BRCA. BRCA patients with low expression of BCL2 and LEF1, as well as high expression of PLK1 and BNIP3 had a poor OS, DSS and DFS. A necroptosis-related prognostic signature with four genes (BCL2, LEF1, PLK1 and BNIP3) was constructed and could serve as prognosis biomarker in BRCA, predicting the OS rate with medium to high accuracy. Moreover, the riskscore correlated with immune infiltration in BRCA. Further comprehensive analysis revealed that the expression of BCL2, LEF1, PLK1 and BNIP3 was correlated with tumor mutation burden, microsatellite instability, drug sensitivity and pathology stage. Previous studies had been extensively studied the role of LEF1, PLK1 and BNIP3 in BRCA and BCL2 was selected for further analysis. The ceRNA network was also identified a lncRNA LINC00665/miR-181c-5p/BCL2 regulatory axis for BRCA. Conclusion: Bioinformatics method was performed to develop a prognostic necroptosis-related prognostic signature containing four genes (BCL2, LEF1, PLK1 and BNIP3) in BRCA. We also constructed a ceRNA network and identified a lncRNA LINC00665/miR-181c-5p/BCL2 regulatory axis for BRCA. Further in vivo and in vitro studies should be conducted to verify these results.